Compromise between conjugation length and charge-transfer in nonlinear optical η5-monocyclopentadienyliron(II) complexes with substituted oligo-thiophene nitrile ligands: synthesis, electrochemical studies and first hyperpolarizabilities - Mendes, Paulo J. (2012)
A systematic series of η5-monocyclopentadienyliron(II) complexes with substituted oligo-thiophene nitrile ligands of general formula [FeCp(P_P)(NCSC4H2nNO2)][PF6] (P_P=dppe, (+)-diop; n=1-3) has been synthesized and characterized. The electrochemical behaviour of the new compounds was explored by cyclic voltammetry. Quadratic hyperpolarizabilities () of the complexes with dppe coligands have been determined by hyper-Rayleigh scattering (HRS) measurements at two fundamental wavelengths of 1.064 and 1.550 m, to uncover the two-photon resonance effect and to estimate static  values. The obtained overall results are found to be better than for the related η5-monocyclopentadienyliron(II) complexes with p-benzonitrile derivatives. Although an increase of the resonant  at 1.064 m with increasing number of thiophene units in the conjugated ligand was found (up to 910 x 10-30 esu), the static values 0 remain practically unchanged, as shown by the 1.550 m measurements. Combined with the electrochemical and spectroscopic data (IR, NMR, UV-Vis), this remarkable evolution of  shows that the increase of conjugation length is balanced by a decrease in charge-transfer efficiency.